Effect of tongue piercing on periodontal and peri‐implant health: A cross‐sectional case‐control study in adults. Issue 2 (4th April 2021) - Ibraheem, Wael I.; S Preethanath, Reghunathan; Devang Divakar, Darshan; Al‐Askar, Mansour; Al‐Kheraif, Abdulaziz A.
Abstract: Objectives: The authors hypothesize that periodontal and peri‐implant inflammatory parameters are poorer in adult patients with tongue piercing compared with controls. The aim was to assess the influence of tongue piercing on periodontal and peri‐implant health status in adults. Methods: Test and control groups comprised of individuals with and without tongue piercing, respectively. A questionnaire was used to collect information about gender, age, duration of tongue piercing and implants in function, jaw location of the implant, reasoning for wearing the tongue ornament, and oral hygiene and ornament cleaning habits. Full‐mouth and peri‐implant plaque index (PI), gingival index (GI), clinical attachment loss (CAL), probing depth (PD) and marginal/crestal bone loss (MBL and CBL, respectively) on mesial and distal surfaces of teeth/implants were recorded. The material (plastic or metal) from which, the bar and ball‐ends of the ornament were fabricated was also recorded. A p  < 0.01 was considered statistically significant. Results: Forty‐eight and 49 individuals were included in the test and control groups, respectively. There was no difference in PI, GI, PD, CAL and MBL (mesial and distal) among individuals in the test and control groups. In the test group, peri‐implant PI ( p  < 0.01), GI ( p  < 0.01), PD ( p  < 0.01) and mesial ( p  < 0.01) and distal ( p  < 0.01) CBL were significantly higher in the anterior mandible compared with implants in other jaw locations. In the control group, there was no difference in peri‐implant PI, GI, PD and CBL around implants placed in both jaws. Conclusion: Wearing tongue piercings could increase the risks of periodontal and peri‐implant diseases particularly in the mandibular anterior segment.